THE ELECTORAL SYSTEM DESIGN ACCORDING TO LAW NUMBER 7 OF 2017 AND ITS OBSTACLES IN ESTABLISHING THE EFFECTIVENESS OF THE PRESIDENTIAL GOVERNMENT IN INDONESIA - Talaba, Renals Y. (Airlangga Development Journal, 2025)
The electoral system currently used in Indonesia has not been able to simplify the party system, and has not changed the behavior of political parties and voter behavior. This will be an obstacle to building the effectiveness of presidential government in Indonesia. Based on these conditions, it is necessary to evaluate the electoral system. In this article, we will discuss the design of the electoral system according to Law Number 7 of 2017 and the obstacles to building a presidential government in Indonesia. For this purpose, the approach used is the Rational Choice Institutionalism (RCI) approach. This approach departs from the view that a series of formal provisions in the form of requirements and procedures will change the behavior of politicians and voters if accompanied by incentives and disincentives. These formal provisions provide incentives for those who implement them and disincentives for those who do not implement them (rule matter). The type of research used is a literature review, which reviews summaries of thoughts from several library sources to develop understanding and theory about the electoral system and its elements, then carries out an analysis of Law Number 7 of 2017. The results of this research show that the design of the electoral system, In the democratic electoral system in Indonesia, it cannot guarantee the effectiveness of government. Keywords: election system design; effectiveness of presidential government; Indonesia.